2017
DOI: 10.5577/intdentres.2011.vol1.no2.5
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cavitated Approach for the Treatment of White Spot Lesions: A Case Report

Abstract: Aim: White spot lesions (WSLs) are the most frequently observed problems in patients with poor oral hygiene. If this problem is left untreated during the initial phase, it will ultimately need major treatment. One treatment alternative in the initial phase is the caries infiltration technique. The aim of this case report is to present the treatment of WSLs by using this technique. Methodology: An 18-year-old female who had WSLs on the buccal surfaces of the lower left canine, first and second premolars and fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…(11,12,18,19) Researchers reported that etching with phosphoric acid affected only the outermost 25µm of the surface. (20) However, superficial phosphoric acid etching causes the caries lesion to extend into the deeper enamel layers resulting in probable cavitation in the future. (20) The penetration depth of 15% HCL etching is more than twice (58 µm) that of phosphoric acid, enabling penetration into the deepest part of the lesion and eliminating the decalcified areas, preventing further attacks.…”
Section: Resin Infiltration Steps and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…(11,12,18,19) Researchers reported that etching with phosphoric acid affected only the outermost 25µm of the surface. (20) However, superficial phosphoric acid etching causes the caries lesion to extend into the deeper enamel layers resulting in probable cavitation in the future. (20) The penetration depth of 15% HCL etching is more than twice (58 µm) that of phosphoric acid, enabling penetration into the deepest part of the lesion and eliminating the decalcified areas, preventing further attacks.…”
Section: Resin Infiltration Steps and Proceduresmentioning
confidence: 99%
“…(20) However, superficial phosphoric acid etching causes the caries lesion to extend into the deeper enamel layers resulting in probable cavitation in the future. (20) The penetration depth of 15% HCL etching is more than twice (58 µm) that of phosphoric acid, enabling penetration into the deepest part of the lesion and eliminating the decalcified areas, preventing further attacks. (13) The surface is then dehydrated with 99% ethanol (ICON Dry) to facilitate the drying process.…”
Section: Resin Infiltration Steps and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…White enamel discolorations are defined as the enamel lesions accompanied with a reduction of the mineral content and consequently render it to opaque and chalky white appearance [1] . They can occur as a consequence of either pre-or post-eruptive damage.…”
Section: Introductionmentioning
confidence: 99%
“…Application of hydrochloric acid as an etchant has been estimated to be superior to 37% orthophosphoric acid gel in removing the outer surface layer of enamel lesion (30-40mm) which hampers resin penetration into the lesion [7,10,21] . Studies reported that etching with orth-phosphoric acid affected the outermost 25mm of the surface layer [1] . Zamorano et al (2017), compared the penetration depth between an infiltrant resin and two adhesive systems but with use of their corresponding etching systems [22] .…”
Section: Introductionmentioning
confidence: 99%